Predictors of Returning to Work after Receiving Specialized Psycho-Oncological Care. (21st February 2020) - van der Lee, Marije; Ranchor, Adelita V.; Garssen, Bert; Sanderman, Robbert; Schroevers, Maya J.; Roelen, Corné
Objectives: This study aimed to identify predictors of returning to work in a group of cancer patients that sought and received help from mental health care institutes specialized in psycho-oncological therapy. Moreover we identified which psychosocial factors were seen as important for returning to work by these patients and therapists working at these institutes. Method: This naturalistic study focused on cancer patients who applied for help at specialized psycho-oncology institutions in the Netherlands. Data were collected before the start of psychological care (T1), and three (T2) and nine (T3) months thereafter. Predictors of return to work were identified based on the opinion of therapists and patients from psycho-oncology institutions in the Netherlands. Predictor scores at T1 were used to predict return to work at T3. Discrimination between patients with and without return to work at T3 was investigated with receiver operating characteristic (ROC) analysis and expressed as the area under the ROC curve (AUC). Results: At T1, 174 participants (79%) were off work due to sickness and 119 (68%) had returned to work at T3. Therapists and patients identified psychological symptoms, quality of life, comorbidity, helplessness, acceptation, mastery, stressful life-events, well-being, and domestic and social functioning as being important for predicting return to work. Domestic functioning was the strongest predictor of return to work at T3. The prediction model including all identified predictor variables did not discriminate between patients with and without return to work at T3, with AUC = 0.652 (95% CI 0.553–0.751). Conclusions: These results suggest that, although psychological symptoms are important at face validity for return to work after cancer, in patients that received help for psychological symptoms, they do not predict return to work.